BUDIDAYA IKAN LELE BERBASIS TEKNOLOGI REKAYASA HORMONAL PADA KELOMPOK MINA TANI GARUDA KECAMATAN SUKABUMI BANDAR LAMPUNG DAN MANDIRI SENTOSA KECAMATAN JATI AGUNG LAMPUNG SELATAN - Tarsim, Tarsim; Mulyasih, Dwi (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2018)
One of the popular freshwater fish to consume In Bandar Lampung is catfish. Increasing market demand of catfish commodities requires more standardized cultivation management. Many catfish farmers have been not informed that there is technical standards for the good fish hatchery (CPIB) and the good fish aqaculture (CBIB) methods which in the form of certificate. The main problem faced by the Minatani Garuda farmers community in Sukabumi is catfish seeds which have decreased seed quality and the Mandiri Sentosa farmers community in Jati Agung is the slow growth of catfish. The problems caused the low level of survival and production of catfish. The general objective of this activity is (1) to increase certified seed productivity, have good quality, and accelerate fish growth in both of the farmers community, (2) increasing the knowledge and skills of partner groups using hormonal engineering technology, (3) build effective partnerships and cooperation between universities and community of fish farmer. The methods used are survey, training, demonstration plots of hormonal technology, mentoring and evaluation of the program success. Based on research, used the hormonal technology in fish is able to give a solution for the community problems. In addition to getting quality seeds at the partner "Minatani Garuda", it can also accelerate the growth of catfish aquaculture in Mandiri Sentosa community. Thus, the availability of catfish commodity in Lampung will always be fulfilled. Based on the training and mentoring result, this activity succeeded in increasing farmers' knowledge about the hormonal technology in Mandiri Sentosa and Minatani Garuda from 10% to 90%. Aquaculture in Sukabumi and Jati Agung has the potential to appy the hormonal technology. Keywords: hormonal technology, fish farmer community, catfish.